Investigating cerebellar neural function in schizophrenia using delay eyeblink conditioning: A pilot fMRI study. (30th October 2020) - Kent, Jerillyn S.; Kim, Dae-Jin; Newman, Sharlene D.; Bolbecker, Amanda R.; O'Donnell, Brian F.; Hetrick, William P.
Highlights: We investigated cerebellar neural activity in individuals with schizophrenia. Patients and controls underwent delay eyeblink conditioning during fMRI. Only controls demonstrated cerebellar activation during eyeblink conditioning. Cerebellar activation was inversely associated with negative symptoms in patients. Results are consistent with the theory of cognitive dysmetria. Abstract: There is accruing evidence of cerebellar abnormalities in individuals with schizophrenia as measured by performance on a variety of tasks believed to be dependent on cerebellar integrity, including delay eyeblink conditioning. There is also evidence of cerebellar dysfunction on a neural level in schizophrenia from both task-based and resting state neuroimaging studies, however few studies have examined cerebellar neural function while the cerebellum is directly recruited in individuals with schizophrenia. In the current pilot study, we examined neural activity during an explicitly cerebellar task in individuals with schizophrenia or schizoaffective disorder and non-psychiatric controls. Participants underwent delay eyeblink conditioning during fMRI. Results indicated eyeblink conditioning impairment in patients as evidenced by a group by time interaction for conditioned responses. A significant cluster of cerebellar activation was present in controls but not patients during the first half of conditioning; there were no significant differences in activation between groups. An ROI analysis focused on the cerebellum in patients revealed two significant clusters that were inversely associated with negative symptom severity. These results are broadly consistent with the theory of cognitive dysmetria, wherein cerebellar abnormalities are theorized to contribute to motor as well as cognitive and affective disturbances in schizophrenia.